2019
DOI: 10.3390/f10020109
|View full text |Cite
|
Sign up to set email alerts
|

Soil Fungal Community in Norway Spruce Forests under Bark Beetle Attack

Abstract: Bark beetle infestation is a widespread phenomenon in temperate forests, which are facing significant weather fluctuations accompanying climate change. Fungi play key roles in forest ecosystems as symbionts of ectomycorrhizal trees, decomposers, or parasites, but the effect of severe disturbances on their communities is largely unknown. The responses of soil fungal communities following bark beetle attack were determined using Illumina sequencing of soil samples from 10 microsites in a mature forest not attack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 53 publications
0
9
1
Order By: Relevance
“…On the other hand, the ECM species community composition on Norway spruce seedlings changed, which was consistent with our hypothesis. When comparing this alteration with one detected in a soil fungal community after bark beetle infestation [20], where Elaphomyces Nees sp. and Russula spp.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…On the other hand, the ECM species community composition on Norway spruce seedlings changed, which was consistent with our hypothesis. When comparing this alteration with one detected in a soil fungal community after bark beetle infestation [20], where Elaphomyces Nees sp. and Russula spp.…”
Section: Discussionmentioning
confidence: 96%
“…T. fibrillosa occupied twice as many seedlings in K2 than in REF, while C. geophilum showed an opposite trend. REF was characterized by the presence of Lactarius, Russula, and Cortinarius species, associated with healthy forests [20,36,37], with some were still found in K1. A similar trend was detected by Peter et al [33], who found T. fibrillosa increased its abundance on seedlings in a locality affected by air pollution with increasing damage intensity, while Russula and Lactarius species preferred sites with lower damage levels.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations